Desastres naturales y lineamientos de planeamiento - Arce Pérez, Isaac (1995)
This, as any other University work, is not exclusive work from whom the signature. The contributions of individuals and institutions were so outstanding, that it would be unfair to ignore your reference in these paragraphs. , In first place, is of Justice remember to who contributed directly in my training in this field, already in the University national of San Martin, where them prof ~ sores is strove by give it best and the base of the career during them first six cycles, or in the University national of engineering, UNI, where concluded them studies of undergraduate as others twenty companions thanks to a Convention Sliscrito with this University and where his experienced flat teaching he forged the first promotions of civil engineers of our young University. At UNI I started the thesis with a first approach to research; "REGIONAL ANALYSIS FOR SAN MARTIN PLANNING" under the asesorainiento of the MgPUR Nemesio Canelo Almeida. The Research Center S...